Bridging the semantic gap in distant communication: providing complementary knowledge within a context. (12th July 2010) - Aye, Nilar; Hattori, Fumio; Kuwabara, Kazuhiro
This paper introduces a multi-agent system to bridge the semantic gap during a conversation between people of different knowledge levels. The system is intended to support smooth communication for providing a definition or explanation of keywords on a specific subject by means of text and graphical format to online users with poor skills. In this framework, software agents act as a personal assistant that monitors the user's information. The Extensible Messaging and Presence Protocol (XMPP) is used for agent message transport and instant messaging (IM) at the same time. Although the conversation keyword is identical, the provision of information is different depending on the user's level of knowledge. The paper describes a sample scenario of computer usage operations in an English composition class that can effectively be applied in a teaching environment. We create domain ontology for students to perform mapping with the teacher's ontology to solve the semantic heterogeneity problem. Bridging the semantic gap helps users to communicate easily without considering the knowledge barrier.